Ketogenic diet for treatment of epilepsy - Rogovik, Alexander L. (College of Family Physicians of Canada, 2010)
QUESTION Families of children with epilepsy now ask about the ketogenic diet at clinic visits. Is it effective and safe to use for treatment of epilepsy? ANSWER The ketogenic diet can be considered an option for children with intractable epilepsy who use multiple antiepileptic drugs. It is a treatment of choice for seizures associated with glucose transporter protein deficiency syndrome (ie, De Vivo disease) and pyruvate dehydrogenase complex deficiency. The diet’s strictness, unpalatability, and side effects limit its use, adversely affecting patients’ compliance and clinical efficacy.